PEMBANGUNAN DAN LINGKUNGAN HIDUP : DILEMA ETIS MANUSIA - Dian Nanlohy (TANGKOLEH PUTAI, 2021)
Various facts and experiences show that the negative impacts of development cause development goals to improve people's welfare to be delayed or not achieved. In preparing development policies with an environmental perspective, environmental considerations become a subsystem that is included in economic development and human resource development. Apart from conquering and fighting for the environment, there is still one more thing that can be done to save the environment, namely designing a sustainable life. The assumption is that if development does not pay attention to the quality of the environment, then the depreciation of natural resources will become increasingly evident. Therefore, the balance between the social environment, the built environment and the natural environment needs to be known and taken into account empirically and objectively in environmentally sound development. This research contains studies related to the Application of Environmental Ethics that must be developed by humans. Humans need to see and understand that a damaged environment is not only part of human moral and ethical responsibility for nature and God's creation that is not damaged, but has become the responsibility of the Christian faith. God the Great Creator. Ecosystem crisis, especially regarding the exploitation of natural resources and pollution, has ethical implications, especially regarding human attitudes and behavior towards nature. This is covered in what is called environmental ethics (eco-ethics).This environmental ethics arises because it is driven by social issues that arise as a result of excessive exploitation of natural resources which has an impact on decreasing environmental quality and pollution. Where environmental ethics is a reflection of humans and nature (environment) which understands that humans and the environment have a close relationship.